Dvoplodna nosečnost po prenosu dveh zarodkov - Bačer-Kermavner, Liljana (Zdravniški vestnik, 2003)
Background. Twin pregnancy rates following the transfer of two embryos in in vitro fertilization (NF) treatment are high. Therefore, the aim of this study was to evaluate twin pregnancy rates in regard to the developmental stage of the embryo, patient age, and cause of infertility. Methods. A retrospective analysis involved 1222 NF procedures. Overall pregnancy rates and twin pregnancy rates following the transfer of two blastocysts or two cleavage-stage embryos were assessed. The blastocyst group was divided into four age subgroups, and into four subgroups by the cause of infertility. Results. After the transfer of two blastocysts or two cleavagestage embryos the overall pregnancy rates (45% vs. 9%) and the twin pregnancy rates (18% vs.5%) were significantly higher in the blastocyst group. The effects of patient age and the transfer of two blastocysts on the overall pregnancy and twin pregnancy rates were significantly greater in the subgroups of patients aged = 39 years = 9%). In the blastocystgroup the twin pregnancy rate was significantly higher in patients with tubal (21%) and endocrinological causes of infertility (24.5%) than in patients with endometriosis (7%) and uterine malformations (12.5%). Conclusions. After the transfer of two blastocysts twin pregnancy rates are significantly higher in patients with tubal factor or endocrinological causes of infertility younger than 34 years. In this population of women the risk of twin pregnancy can be avoided by the transfer of a single embryo most developed blastocyst.
Keywords: Blastocista; Blastocyst; Dvojčka; Embryo Transfer; fertilization; Fertilization In Vitro; human pregnancy; in vitro fertilization; Infertility, Female; Neplodnost ženska; Nosečnost; Nosečnost večplodna; oploditev; Oploditev in vitro; porodništvo; Pregnancy; Pregnancy, Multiple; prenos zarodkov; Twins; Zarodek, prenos